Developing a Digital Circular Economy Business Model for SIPETRA in Jatiluwih Village, Bali - I Gede Dody Okta Biantara; Marmaiyatno Marmaiyatno; I Made Kresna Dana (Information Technology and Science (ITScience), 2026)
Waste management in tourism villages has become a major environmental challenge due to increasing waste generation from tourism activities and limited local infrastructure. Jatiluwih Village, a UNESCO World Heritage site in Bali, faces this issue as tourism growth produces more domestic and organic waste. Although several studies have examined community-based waste initiatives, research integrating strategic analysis, participatory validation, and business model innovation remains limited. This study aims to design a sustainable business model for SIPETRA (Waste Management and Technology System for Waste Transformation) as a community-based circular economy solution supported by digital technology. Unlike previous studies, this research integrates SWOT, Delphi, BMC, and BOS into a unified framework to develop a digital circular economy model tailored to rural tourism contexts. The research employed a descriptive qualitative method through field observation, interviews, questionnaires, and literature analysis. Data were processed using SWOT and Delphi techniques to identify strategic factors, followed by the formulation of the Business Model Canvas and Blue Ocean Strategy. The results show that SIPETRA’s internal capacity is moderately weak (IFAS = 2.45), while external opportunities are strong (EFAS = 3.01), placing the model in the WO quadrant. Consensus from 12 experts (Kendall’s W = 0.78) identified four strategic priorities: human resource improvement, digital transformation, product quality enhancement, and partnership-based funding. The BOS analysis generated innovative programs such as the SIPETRA app, Eco-Coin reward system, and Green Experience Center to create a “Jatiluwih Circular Living Experience.” This study concludes that the integrated analytical framework effectively transforms waste management into a self-sustaining digital circular economy model that supports environmental sustainability, social empowerment, and green tourism. The findings provide theoretical contributions to digital circular economy literature and practical implications for tourism villages seeking scalable and community-driven waste management solutions.